Preferensi Konsumen dalam Pembelian Produk yang Dipasarkan di Supermarket TIP TOP Cabang Ciputat - Sururi, M. (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2021)
The halal label is the output of LPPOM MUI for products that have passed the halal certification process. The study analyzes the effect of product halal labels on purchasing decisions and to find out how much influence it has on consumers of the TIP TOP Supermarket Ciputat. The research method uses descriptive correlation with a quantitative approach. The findings of this study state that the halal label on the product has a significant positive effect on consumer purchasing decisions at the TIP TOP Ciputat Supermarket, with a correlation significance value of 0.420 and a coefficient of determination of 17.64%. While the other 82.36% is the influence of other factors.